Hypercompetition: Managing the Dynamics of Strategic ManeuveringHypercompetition: Managing the Dynamics of Strategic Maneuvering, by D'AveniRichard A.. New York: Free Press, 1994. - Veliyath, Rajaram (Academy of Management Review, 1996)
The article reviews the book “Hypercompetition: Managing the Dynamics of Strategic Maneuvering,” by Richard A. D'Aveni.